Social security system in Malaysia : the impact of aging populations. - Tengku Abdul Hamid, Tengku Aizan; I., Rahimah; Chai, S. T. (2013)
Malaysia's social security system is a mix of social insurance, social assistance, social allowances, national provident fund, voluntary retirement savings, employer liability measures, and other arrangements under the respective public health, employment and education systems. Historically, the country has a long track record of combating poverty through specific rural and urban development plans. This paper outlines the various social security programmes in Malaysia that offers protection for old age, disability, work injury and deaths, sickness and maternity, unemployment, at-risk families and children, medical care, illiteracy as well as other form of vulnerabilities. Malaysia follows an active labour market policy where both the Employees Provident Fund (EPF) and the Social Security Organization (SOCSO) play a central role in the country's multi-pillar social protection system. The mandatory savings and social insurance scheme covers private sector workers and non-pensionable civil service staff. Public sector workers are covered under a pension scheme directly funded through tax revenues, while informal sector workers have to rely on a mix of auxiliary social insurance, social assistance and voluntary savings schemes. Financial assistance programmes for single mothers, older persons and families with children under the Department of Social Welfare Malaysia are means-tested transfers with limited income replacement benefits. Other programmes and initiatives such as the microcredit scheme by Amanah Ikhtiar Malaysia (AIM), training schemes under the Human Resource Development Fund (HRDF) and various entrepreneurial development programs (e.g. lAZAM) focus on income generation and job creation. Subsidies and federal expenditure on health, education and housing is indicative of the government's growth priorities. After the Asian financial crisis and subsequent US-EU global economic recession, weaknesses in a minimalist welfare model characterized by years of low public spending in social services began to show. Malaysia started introducing novel social allowances and other populist measures benefitting targeted populations. The social security system in Malaysia is reflective of the country's economic development principles which emphasize wealth creation rather than redistributive or insurance concepts. With a rapidly ageing population and peaking demographic window, the government must consider new or complementary approaches to create a sustainable mix of social security programmes that balances individual rights and responsibility through collective sharing or pooling.